Ethnic Drag Performing Race, Nation, Sexuality in West Germany - Sieg, Katrin (University of Michigan Press, 2002)
The Holocaust is considered a singularly atrocious event in human history, and many people have studied its causes. Yet few questions have been asked about the ways in which West Germans have "forgotten," unlearned, or reconstructed the racial beliefs at the core of the Nazi state in order to build a democratic society. This study looks at ethnic drag as one particular kind of performance that reveals how postwar Germans lived, disavowed, and contested "Germanness" in its complex racial, national, and sexual dimensions.